Long-term outcomes following percutaneous microwave ablation for colorectal cancer liver metastases. (31st December 2022) - Vogl, Thomas J.; Zitsch, Maximilian; Albrecht, Moritz; D'Angelo, Tommaso; Basten, Lajos; Gruber-Rouh, Tatjana; Nour-Eldin, Nour-Eldin A.; Naguib, Nagy N. N.
Abstract: Purpose: To evaluate the overall survival (OS), local progression-free survival (PFS) and prognostic factors of patients with colorectal cancer liver metastases (CRLM) undergoing microwave ablation (MWA). Method: A total of 132 patients were retrospectively enrolled who had been treated between 2010 and 2018. For the evaluation of survival rates, all patients were divided according to their indications (curative n = 57 and debulking (patients with additional non-target extrahepatic metastases) n = 75). In total, 257 ablations were evaluated for prognostic factors: number of liver metastases, primary tumor origin (PTO), diameter and volume of metastases, duration and energy of ablation. Results: The OS was 32.1 months with 93.2% of patients free from recurrence at 28.3 months (median follow-up time). The one- year and three-year OS were 82.72% and 41.66%, respectively. The OS and recurrence-free survival of the curative group were statistically significantly higher than the debulking group ( p < .001). Statistically significant prognostic factors for OS included the location of the primary tumor ( p < .038) and the number of metastases (all p < .017). Metastasis diameter and volume and ablation duration and energy had no significant correlation with survival ( p > .05). Conclusions: Satisfactory OS and local tumor PFS can be achieved in patients with CRLM using MWA with the number of metastases and the location of the primary tumor influencing the outcome of patients. The metastasis's size and the duration and energy used for ablation were not of significant prognostic value.